Thickness-dependence electrical characterization of the one-dimensional van der Waals TaSe3 crystal - Kim, Bum Jun; Jeong, Byung Joo; Oh, Seungbae; Chae, Sudong; Choi, Kyung Hwan; Nasir, Tuqeer; Lee, Sang Hoon; Lim, Hyung Kyu; Choi, Ik Jun; Hong, Min Ki; Yu, Hak Ki; Lee, Jae Hyun; et al. (Materials, 2019)
Needle-like single crystalline wires of TaSe3 were massively synthesized using the chemical vapor transport method. Since the wedged-shaped single TaSe3 molecular chains were stacked along the b-axis by weak van der Waals interactions, a few layers of TaSe3 flakes could be easily isolated using a typical mechanical exfoliation method. The exfoliated TaSe3 flakes had an anisotropic planar structure, and the number of layers could be controlled by a repeated peeling process until a monolayer of TaSe3 nanoribbon was obtained. Through atomic force and scanning Kelvin probe microscope analyses, it was found that the variation in the work function with the thickness of the TaSe3 flakes was due to the interlayer screening effect. We believe that our results will not only help to add a novel quasi-1D block for nanoelectronics devices based on 2D van der Waals heterostructures, but also provide crucial information for designing proper contacts in device architecture.
Keywords: Chemical vapor transport; Electrical characterization; Mechanical exfoliation; Scanning Kelvin probes; Single-crystalline wires; TaSe3; Van der waals; Van Der Waals interactions; Mechanical exfoliation; Scanning Kelvin probing microscopy; TaSe3; Van der Waals crystal; Work function